Ibn Sinā's psychology: the substantiation of soul values in Islamic education - Prasetia, Senata Adi; Rofiq, Arif Ainur; Sawai, Rezki Perdani; Sawai, Joki Perdani (IAIN Salatiga, 2022)
This article presents the concept of the soul from Ibn Sinā's perspective and its substantiation in Islamic education. The soul is one of the major psychological topics which has been explored by Muslim scholars. Among them was Ibn Sinā, a Muslim philosopher, who emphasized the study of the human soul. His mental conception of the soul was so well-developed that it received much attention and appreciation from later Islamic philosophers such as al-Ghazāli, Fakhruddin al-Rāzi, Ibn Rushd and Western scholars. This article explores Ibn Sinā's concept of the soul and its substance in Islamic education. The methodology employed is a literature review together with qualitative research using exploratory, descriptive, and analytical approaches. Ibn Sinā argued that the soul is a living spiritual substance inspiring the body and forms the infrastructure for acquiring knowledge and transforming it in real life. In contrast to the body, the soul is immaterial and eternal. Islamic education cannot be separated from the psychological elements elucidated by Ibn Sinā and must incorporate relevant psychological aspects in order to fully develop the potential of students towards becoming exemplary human beings (insān kāmil).